ANALISIS TINGKAT KEPUASAN PELANGGAN SHOPEE TERHADAP E-SERVICE QUALITY DI KOTA PEKANBARU - , Rendra Wasnury, Dewi Sartika , Taufiqurrahman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to analyze the level of customer satisfaction with the e-Service Quality provided by Shopee and to find out which Shopee service attributes need to be prioritized to improve and meet customer satisfaction. The variables used in this study are the dimensions of e-Service Quality, which consist of; efficiency, system availability, fulfillment, privacy, responsiveness, compensation, and contacts. The method chosen in this research is the Customer Satisfaction Index (CSI) method, the e-Service Quality method, and the Importance Performance Analysis (IPA) method. This research was conducted on Shopee users who live in Pekanbaru City, with a total sample of 120 respondents using a purposive sampling method. Testing and data processing was carried out with the help of SPSS 21 and Ms. Excel. The results showed that the overall Shopee customer satisfaction index in Pekanbaru City based on the CSI calculation was "satisfied" with a value of 72.97%. Based on the overall e-Servqual calculation -0.32, which means that the service quality from Shopee as a whole is not maximized. Based on the results of the IPA calculation, 3 attributes need to be prioritized for improvement or improvement (quadrant I). 10 attributes that need to be maintained (quadrant II), 10 attributes that have low priority by the user (quadrant III), and 1 attribute that can be removed (quadrant IV). Keywords: Customer Satisfaction, e-Service Quality, Customer Satisfaction Index (CSI), Importance Performance Analysis (IPA)